Optimized Synthesis of Magnesium Oxide Nanoparticles as Bactericidal Agents - Mohammad Moslem Imani; Mohsen Safaei (Journal of Nanotechnology)
Increased antibiotic resistance of microorganisms as well as the need to reduce health-care costs necessitates the production of new antimicrobials at lower costs. For this reason, this study was aimed to optimize the synthesis of magnesium oxide nanoparticles with the greatest antibacterial activity. In this study, 9 experiments containing different proportions of the factors (magnesium nitrate, NaOH, and stirring time) effective in the synthesis of magnesium oxide nanoparticles were designed using the Taguchi method. Magnesium oxide nanoparticles were synthesized using the coprecipitation method, and their antibacterial activity was evaluated using colony-forming unit (CFU) and disk diffusion. Morphology, crystalline structure, and size of synthesized nanoparticles were investigated using Fourier transform infrared (FTIR), X-ray diffraction (XRD), and scanning electron microscope (SEM). The optimum conditions (0.2 M magnesium nitrate, 2 M NaOH, and 90 min stirring time) for the synthesis of magnesium oxide nanoparticles with the greatest antibacterial activity were determined using the Taguchi method. The results of colony-forming unit and disk diffusion revealed the optimal antibacterial activity of synthesized nanoparticles against Staphylococcus aureus and Escherichia coli bacteria. The results obtained from FTIR and XRD analyses confirmed the synthesis of nanoparticles with favorable conditions. Also, according to the SEM image, the average size of synthesized nanoparticles was determined to be about 21 nm. According to the results, magnesium oxide nanoparticles can significantly reduce the number of Gram-positive and Gram-negative bacteria and can be used as an appropriate alternative to commonly used antibacterial compounds in order to tackle drug resistance among pathogens.